Analisis Faktor-Faktor Yang Mempengaruhi Kebijakan Hutang Perusahaan Dengan Moderasi Profitabilitas - Christie Arlim Setiawan, Nurainun Bangun (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This research aims to examine the effect of institutional ownership, free cash flow and sales growth moderated by profitability on debt policies in the manufacturing and property sectors listed on the Indonesia Stock Exchange during the period 2017 - 2019. This research was conducted by taking 33 sample companies, using purposive sampling method and processed using SPSS version 25. Partial test results (t test) show that institutional ownership and free cash flow have no significant effect on debt policy, while sales growth and profitability which moderates institutional ownership and sales growth shows a significant effect on debt policy. The implication of this research is to increase supervision through institutional ownership towards debt policies that are created and regulated by management and the use of adequate free cash flow to avoid the use of external funding.